Periprosthetic Hip Heterotopic Ossification after Electrocution - Coden, Gloria; Johnson, Kurt V.; Bono, Olivia; Bono, James V. (The Journal of Hip Surgery, 2024)
Background Heterotopic ossification is not only a common occurrence following total hip arthroplasty, but also may follow burn injuries. Uncommonly, this entity may become symptomatic when associated with a hip replacement and even less commonly presents in a delayed fashion years after the procedure.Case Presentation We describe a case in which symptomatic periprosthetic heterotopic ossification was identified years after total hip replacement, but only months following an electrical injury.Conclusion Patients with prosthetic joint replacements may be at risk for symptomatic periprosthetic heterotopic ossification following an electrocution event due to electrical conduction through the prosthesis and surrounding tissues.
Keywords: heterotopic ossification; hip arthroplasty; periprosthetic; electrocution